2005
DOI: 10.1016/j.bcp.2004.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral benzodiazepine receptor (PBR) ligand cytotoxicity unrelated to PBR expression

Abstract: Category

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 52 publications
1
25
0
1
Order By: Relevance
“…By using RT-PCR, no PBR transcript was shown previously by Canat et al (1993) and Hans et al (2005). On the contrary, some evidences have demonstrated that PBR mRNA is expressed in human Fas-resistant T-cell line Jurkat (Decaudin et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…By using RT-PCR, no PBR transcript was shown previously by Canat et al (1993) and Hans et al (2005). On the contrary, some evidences have demonstrated that PBR mRNA is expressed in human Fas-resistant T-cell line Jurkat (Decaudin et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…The PBR amino acidic substitution H162R may explain why some authors have not detected protein in Jurkat cells by using the monoclonal anti-PBR 8D7 antibody (Carayon et al, 1996;Hans et al, 2005), which recognized the human PBR C-terminal region that contains His162 instead of arginine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of greater concern is that ligands have been shown to participate in cellular functions independently of the TSPO (Gonzalez-Polo et al, 2005;Hans et al, 2005;Walter et al, 2005). Also perplexing is the fact that the so-called agonists and antagonists of the TSPO often exert the same effects (Chelli et al, 2001).…”
mentioning
confidence: 98%
“…Interestingly, PK11195, but not Ro5-4864, exerts anti-inflammatory actions on mononuclear phagocytes, regulating the release of IL-1b (Klegeris et al, 2000). In addition, it is important to consider that both PK11195 and Ro5-4864 may have additional cellular actions that are independent of TSPO (Gonzalez-Polo et al, 2005;Hans et al, 2005;Papadopoulos et al, 2006;Walter et al, 2005). Therefore, PK11195 and Ro5-4864 may have different and complementary mechanisms of action on different cell populations.…”
Section: Discussionmentioning
confidence: 95%